Cultivating natures: movements in South African permaculture - Kruger, Elizabeth (My University, 2017)
Environmental history and anthropology are disciplines yet in their infancy in South Africa, and still leave many opportunities for further research. The global permaculture movement has emerged as one amongst an array of environmental movements in South Africa that seek alternatives to industrialised capitalist economics which have been identified by many observers as problematic and deleterious to both human and ecological ‘systems’. This research explores permaculture practice as an environmental social movement in the South African context, drawing on a wide array of theory including environmental anthropology, environmental history, social movements theory and ‘whiteness’ studies, amongst others. These bodies of theory have been used to analyse the research data drawn primarily from established anthropological methods of participant observation, narrative elicitation through deep and open-ended interviews and the observation of social and land use practices in particular detailed case studies. The research findings indicated that while permaculture ideology proposed an alternative utopian approach to human-ecological relationships associated with the trappings of neoliberal economic models for development and conservation, the actual practice of permaculture - communally-based resource management and the realisation of these ideals - while developing knowledge around localised sustainable land-use strategies, appeared to necessitate the regulation of social relations and resource access, alignment with the state’s environmental and land-use policies and were largely made possible by white privilege rooted in the country’s colonial and apartheid history. The research highlighted the need to recognise the social and historical specificity of permaculture ideology and practice within the South African context.
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy (Anthropology), 2017
Keywords: Economic development--Environmental aspects--South Africa.; Economic development--Environmental aspects--South Africa.